microRNA: Basic Science From Molecular Biology to Clinical Practice - Santulli, Gaetano (Advances in Experimental Medicine and Biology, 2015)
This volume explores microRNA pathophysiology, focusing on basic concepts in molecular and cellular biology. Chapters contributed by leading scientists examine recently discovered pathways in several processes, including aging, diabetes, cardiovascular disease, hematopoiesis, and mitochondrial fitness. The authors contextualize microRNAs within epigenetics and micropeptidomics, angiongenesis and atherosclerosis, endometrial pathophysiology, and more. Throughout, numerous color photographs, diagrams of molecular pathways, and tables enhance the text. microRNA: Basic Science is an ideal companion to both microRNA: Medical Evidence and microRNA: Cancer. Taken together, these three books provide a state-of-the-art overview of this rapidly-expanding and fascinating field, from the molecular level to clinical practice. It will be invaluable to medical students, physicians, and researchers, as a complete and unique guide in the exploration of microRNA in basic science, cancer and clinical practice.